DEVELOPING AN ENGLISH WEBSITE-BASED LEARNING MEDIA AS THE LEARNING ASSISTANCE FOR 7 GRADERS - Pujiani, Tri; Ramdania, Nofa Elok; Halimah, Nur (Universitas 17 Agustus 1945 Semarang, 2024)
The creation of website-based learning media in English as a learning aid for students is an important topic in today's digital era. This article discusses the development process of an educational website that uses interactive content to help students learn topics by including various features, such as fun video animations, interactive games, and quizzes. Users and experts feedbacks are the important part of the development cycle, allowing for continuous improvement and refinement of the website. This project was conducted using the Research and Development method with the 4D model, namely Define, Design, Development, and Disseminate. The research results were obtained after the web-based learning media was presented and validated by teacher, media expert, and material expert, so that the media was valid and suitable for use. This website has several advantages, such as flexibility of access, responsiveness to various screen sizes, and the ability to facilitate students' concept understanding. Keywords: learning media, website-based learning, Research and Development, Junior High School